Sistem Informasi Pengolahan Data Siswa Praktek Kerja Lapangan Berbasis Web Menggunakan Metode Codeigniter - Fikri Rahmat Junaedi; Rais Farid; Putri Anggi Nurhaliza Utami (Jurnal Riset Multidisiplin Edukasi, 2025)
This research is entitled "Web-Based Information System for Data Processing Student Field Work Practices (PKL) at SMKN 2 Purwakarta Using the CodeIgniter (CI) Method". This system is designed to facilitate the process of managing and monitoring student data undergoing PKL at SMKN 2 Purwakarta. The problem formulation in this research is how to design and implement a web- based system that is able to optimize PKL student data processing efficiently and accurately, reduce the potential for errors in data input, and increase information transparency between students, supervisors and PKL coordinators. The research method used in developing this system is a qualitative method, which aims to understand and analyze the needs and problems faced by users in the process of processing PKL student data. This research also uses the CodeIgniter (CI) framework as a web-based development platform to ensure the system built has an organized, modular structure and is easy to maintain. The main aim of this system is to increase the efficiency of data processing for PKL students at SMKN 2 Purwakarta, provide faster and more accurate access to information for all related parties, and support monitoring of student progress while undergoing PKL.